Gut microbial and metabolomic profiles after fecal microbiota transplantation in pediatric ulcerative colitis patients. Issue 9 (13th July 2018) - Nusbaum, David J; Sun, Fengzhu; Ren, Jie; Zhu, Zifan; Ramsy, Natalie; Pervolarakis, Nicholas; Kunde, Sachin; England, Whitney; Gao, Bei; Fiehn, Oliver; Michail, Sonia; Whiteson, Katrine
ABSTRACT: Ulcerative colitis is a chronic inflammatory disease of the colon that carries a significant disease burden in children. Therefore, new therapeutic approaches are being explored to help children living with this disease. Fecal microbiota transplantation (FMT) has been successful in some children with ulcerative colitis. However, the mechanism of its therapeutic effect in this patient population is not well understood. To characterize changes in gut microbial and metabolomic profiles after FMT, we performed 16S rRNA gene sequencing, shotgun metagenomic sequencing, virome analysis and untargeted metabolomics by gas chromatography-time of flight-mass spectrometry on stool samples collected before and after FMT from four children with ulcerative colitis who responded to this treatment. Alpha diversity of the gut microbiota increased after intervention, with species richness rising from 251 (S.D. 125) to 358 (S.D. 27). In responders, the mean relative abundance of bacteria in the class Clostridia shifted toward donor levels, increasing from 33% (S.D. 11%) to 54% (S.D. 16%). Patient metabolomic and viromic profiles exhibited a similar but less pronounced shift toward donor profiles after FMT. The fecal concentrations of several metabolites were altered after FMT, correlating with clinical improvement. Larger studies using a similar multi-omics approach may suggest novel strategies for the treatment of pediatric ulcerative colitis. Abstract : Gut microbial and metabolomic profiles are altered after fecal microbiota transplantation in pediatric ulcerative colitis patients.